PENGARUH PENERAPAN E-SAMSAT, KUALITAS PELAYANAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN PAJAK KENDARAAN BERMOTOR DI KOTA BATAM - Tapun, Ledi Angreni Tapun (SCIENTIA JOURNAL, 2024)
The purpose of this research is to obtain evidence that can influence for application in e-samsat, Tax Employee Service, And Tax Sunctions on Tax Payer Compliance paying vehicle tax in Batam City. 100 responders served as the study’s sample. Data was gathered via a questionnaire. Several research techniques are applied to fulfill the goal of the research including and descriptive statistical analysis, validity test, reability test,test classical assumption (normality test, multicollinearity test, heteroscedasticity test), multiple regression analysis, hipotesys test (t test, f test, coefficient determination test). The result of this study showed that the influence application of e-samsat, Tax Employee Service and tax sanctions have effect dan signifikan on tax compliance paying vehicle tax in Batam City.